Islam and Sufism in Goethe‘s Works - Edibe Nuray Saatci (Tasavvuf Araştırmaları Enstitüsü Dergisi, 2022)
As is well known, Johann Wolfgang Goethe (1749-1832) is Germany's most famous poet and literary figure of all time. Goethe received a very good education and his knowledge and curiosity were not limited to literature. He was versatile; he was interested in natural sciences, painting, music, philosophy, theology and developed himself in these branches as well. He took lessons in various languages at an early age. In addition to French, English, Latin and Greek, he was also fluent in Hebrew and took an interest in Arabic. He studied law and served as a minister of state. Goethe, who grew up in a Protestant family, had a very good command of Christian doctrine and the Bible, both in language and content. In his 83 years of life, Goethe always pursued the truth and in this context he studied many religions. According to the famous Goethe expert Prof. Katharina Mommsen, Goethe found Islam the closest to his understanding of religion, especially in matters such as the unity of God, the manifestations of God, belief in prophets, submission to God, belief in fate and accident. He started reading the Qur'an at the age of 23 and compiled a German summary of the Qur'an (Koran-Auszüge) consisting of 11 suras.